Assessing full thickness oral mucosal grafting: complications and postoperative outcomes in a broad collective of patients. Issue 1 (10th February 2020) - Pilger, Daniel; von Sonnleithner, Christoph; Bertelmann, Eckart
Abstract : Background: Conjunctival defects can be repaired with several mucosal tissues. The simplicity of harvesting oral mucosa and its wide availability makes it the preferred graft tissue for all indications requiring mucosal grafting. Through analysing the postsurgical outcomes and rate of revisions, this study explores the suitability of oral mucosa grafts, depending on the initial diagnosis. Methods: We reviewed all the files of patients with a history of oral mucosal graft surgery, performed at our clinic between 2012 and 2018, focusing on complications and revision rates. Results: In total, we analysed 173 oral mucosa grafts in 131 patients. The most common initial diagnosis was tumour resection, followed by surgical complications, postenucleation socket syndrome, trauma and ocular surface disorders. Complication and revision rates depended highly on the initial diagnosis. Revision rates were highest if the initial diagnosis included ocular surface disorders or chemical trauma. Conclusions: Oral mucosa grafting (OMG) is the most effective treatment for a wide range of ocular conditions involving conjunctival defects. Conjunctival defects that result from trauma or cicatricial surface diseases seem less suitable for OMG and may benefit from alternative graft tissue or treatment options.